Four-point functions of 1/2-BPS operators of any weights in the supergravity approximation - Gleb Arutyunov; Rob Klabbers; Sergei Savin (Journal of High Energy Physics, 2018)
Abstract We present the computation of all the correlators of 1/2-BPS operators in N=4 $$ \mathcal{N}=4 $$ SYM with weights up to 8 as well as some very high-weight correlation functions from the effective supergravity action. The computation is done by implementing the recently developed simplified algorithm in combination with the harmonic polynomial formalism. We provide a database of these results attached to this publication and additionally check for almost all of the functions in this database that they agree with the conjecture on their Mellin-space form.